(untitled) - Bossidy, Larry (New York, 2002)
The book that shows how to get the job done and deliver results . . . whether you’re running an entire company or in your first management job. Larry Bossidy is one of the world’s most acclaimed CEOs, a man with few peers who has a track record for delivering results. Ram Charan is a legendary advisor to senior executives and boards of directors, a man with unparalleled insight into why some companies are successful and others are not. Together they’ve pooled their knowledge and experience into the one book on how to close the gap between results promised and results delivered that people in business need today.
Keywords: Quản trị,Management